If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3x + -5) = (x + -10) + -25 Reorder the terms: -4(-5 + 3x) = (x + -10) + -25 (-5 * -4 + 3x * -4) = (x + -10) + -25 (20 + -12x) = (x + -10) + -25 Reorder the terms: 20 + -12x = (-10 + x) + -25 Remove parenthesis around (-10 + x) 20 + -12x = -10 + x + -25 Reorder the terms: 20 + -12x = -10 + -25 + x Combine like terms: -10 + -25 = -35 20 + -12x = -35 + x Solving 20 + -12x = -35 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 20 + -12x + -1x = -35 + x + -1x Combine like terms: -12x + -1x = -13x 20 + -13x = -35 + x + -1x Combine like terms: x + -1x = 0 20 + -13x = -35 + 0 20 + -13x = -35 Add '-20' to each side of the equation. 20 + -20 + -13x = -35 + -20 Combine like terms: 20 + -20 = 0 0 + -13x = -35 + -20 -13x = -35 + -20 Combine like terms: -35 + -20 = -55 -13x = -55 Divide each side by '-13'. x = 4.230769231 Simplifying x = 4.230769231
| 2(2c-1)-4=2c+6 | | -4(t+5)=8 | | 12x+4=2(6x+1) | | 37-12=5(x-7) | | x-40=45 | | x^2+3=17 | | 2(x-2)+4=2x | | x^2-12x+48=0 | | 3x-100=45 | | x^2+6x+C=0 | | 29+3y-9=10y-10-2y | | -9+(-6)= | | x+25+4x=-25-4x-31 | | 9t-27=0 | | 7(w+1)-4w=w-8 | | -4=-6-2b | | -20+12+(-29)= | | 3(x-4)=28+4x | | (4+2)+y= | | 12-0.33u=3 | | 6y+3-8y=-37 | | .5x+4=18-.6x | | 7x+27=90 | | 2b+3=-5 | | 2z-31=-9z+28 | | 5n+7=22 | | 16-3n=-11 | | -7-5(6-2x)=(-3x-5) | | r+1/17=0 | | -2(3w+5)=7w-4-w | | 4(m+3)+7=4m+19 | | 2+10(3n+7)= |